2014
DOI: 10.11113/jt.v69.3111
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Fingerprint Image Pre-processing

Abstract: Fingerprints are the most widely used form of human identification and verification due to their uniqueness and permanence. For that reason, many Automatic Fingerprint Identification Systems (AFIS) have been commercially produced and accepted by the international community. Though their performance is good, there is still room for improvement. One of the main concerns is poor fingerprint images that are caused by capturing devices. Thus, to improve the efficiency of AFIS, both image enhancement and feature ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Fingerprint pre-processing usually involves enhancing the quality of the fingerprint image, i.e., producing high contrast between ridges and valleys, to facilitate minutiae-based local feature extraction. 15 Fig. 1 Various components involved in minutiae feature-based FBS.…”
Section: Fingerprint Biometric System: An Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Fingerprint pre-processing usually involves enhancing the quality of the fingerprint image, i.e., producing high contrast between ridges and valleys, to facilitate minutiae-based local feature extraction. 15 Fig. 1 Various components involved in minutiae feature-based FBS.…”
Section: Fingerprint Biometric System: An Overviewmentioning
confidence: 99%
“…In the case of Watchlist ROC plots, ideally, the curves are expected to deviate marginally for DIR and show significant variations on FAR. But the plots from Figs 15. 19 demonstrated that the identification rate reduced considerably compared to FAR.…”
mentioning
confidence: 96%
“…Pre-processing is the stage to normalize the results of the fingerprint image acquisition. Preprocessing consists of sequential processing stages: image cropping, grayscale conversion, image improvement, binary image conversion, and thinning [1].…”
Section: Fingerprint Image Pre-processingmentioning
confidence: 99%
“…One of them focuses on filtering techniques. Kaur and Kaur, Abbod et al, Sawant and Deore, and Rajin and Ajith [5][6][7][8] only listed published work on fingerprint image enhancement.…”
Section: Related Workmentioning
confidence: 99%
“…Biometric sample quality and performance should be the main aspects when assessing a method for fingerprint image enhancement. However, most surveys on fingerprint image enhancement do not perform any assessment at all [2][3][4][5][6][7][8]. Only three publications evaluated biometric performance for a single biometric feature extraction considering at most three datasets [9][10][11].…”
Section: Introductionmentioning
confidence: 99%